Azologization and repurposing of a hetero-stilbene-based kinase inhibitor: towards the design of photoswitchable sirtuin inhibitors - Grathwol, Christoph W.; Wössner, Nathalie; Swyter, Sören; Smith, Adam C.; Tapavicza, Enrico; Hofstetter, Robert K.; Bodtke, Anja; Jung, Manfred; Link, Andreas (Beilstein Journal of Organic Chemistry, 2019)
The use of light as an external trigger to change ligand shape and as a result its bioactivity, allows the probing of pharmacologically relevant systems with spatiotemporal resolution. A hetero-stilbene lead resulting from the screening of a compound that was originally designed as kinase inhibitor served as a starting point for the design of photoswitchable sirtuin inhibitors. Because the original stilbenoid structure exerted unfavourable photochemical characteristics it was remodelled to its heteroarylic diazeno analogue. By this intramolecular azologization, the shape of the molecule was left unaltered, whereas the photoswitching ability was improved. As anticipated, the highly analogous compound showed similar activity in its thermodynamically stable stretched-out (E)-form. Irradiation of this isomer triggers isomerisation to the long-lived (Z)-configuration with a bent geometry causing a considerably shorter end‐to‐end distance. The resulting affinity shifts are intended to enable real‐time photomodulation of sirtuins in vitro.
Keywords: azo compounds; epigenetics; photoswitch; sirtuins; stilbenes

(untitled) - Schiedel, M.; Robaa, D.; Rumpf, T.; Sippl, W.; Jung, M. (Med. Res. Rev., 2018)

(untitled) - Frye, R. A. (Biochem. Biophys. Res. Commun., 2000)

(untitled) - Vaziri, H.; Dessain, S. K.; Eaton, E. N.; Imai, S.-I.; Frye, R. A.; Pandita, T. K.; Guarente, L.; Weinberg, R. A. (Cell, 2001)

(untitled) - Perrod, S.; Cockell, M. M.; Laroche, T.; Renauld, H.; Ducrest, A.-L.; Bonnard, C.; Gasser, S. M. (EMBO J., 2001)

(untitled) - Tanno, M.; Sakamoto, J.; Miura, T.; Shimamoto, K.; Horio, Y. (J. Biol. Chem., 2007)

(untitled) - Rumpf, T.; Schiedel, M.; Karaman, B.; Roessler, C.; North, B. J.; Lehotzky, A.; Oláh, J.; Ladwein, K. I.; Schmidtkunz, K.; Gajer, M.; Pannek, M.; Steegborn, C.; et al. (Nat. Commun., 2015)

(untitled) - North, B. J.; Verdin, E. (PLoS One, 2007)

(untitled) - Schwer, B.; North, B. J.; Frye, R. A.; Ott, M.; Verdin, E. (J. Cell Biol., 2002)

AOP Orphan Pharmaceuticals AG (2017)

(untitled) - Süssmuth, S. D.; Haider, S.; Landwehrmeyer, G. B.; Farmer, R.; Frost, C.; Tripepi, G.; Andersen, C. A.; Di Bacco, M.; Lamanna, C.; Diodato, E.; Massai, L.; Diamanti, D.; et al. (Br. J. Clin. Pharmacol., 2015)

(untitled) - Chopra, V.; Quinti, L.; Kim, J.; Vollor, L.; Narayanan, K. L.; Edgerly, C.; Cipicchio, P. M.; Lauver, M. A.; Choi, S. H.; Silverman, R. B.; Ferrante, R. J.; Hersch, S.; et al. (Cell Rep., 2012)

(untitled) - Outeiro, T. F.; Kontopoulos, E.; Altmann, S. M.; Kufareva, I.; Strathearn, K. E.; Amore, A. M.; Volk, C. B.; Maxwell, M. M.; Rochet, J.-C.; McLean, P. J.; Young, A. B.; Abagyan, R.; et al. (Science, 2007)

(untitled) - Pillai, V. B.; Bindu, S.; Sharp, W.; Fang, Y. H.; Kim, G.; Gupta, M.; Samant, S.; Gupta, M. P. (Am. J. Physiol.: Heart Circ. Physiol., 2016)

(untitled) - Lu, Y.; Wang, Y.-d.; Wang, X.-y.; Chen, H.; Cai, Z.-j.; Xiang, M.-x. (Int. J. Cardiol., 2016)

(untitled) - He, X.; Zeng, H.; Chen, J.-X. (Int. J. Cardiol., 2016)

(untitled) - Bellizzi, D.; Rose, G.; Cavalcante, P.; Covello, G.; Dato, S.; De Rango, F.; Greco, V.; Maggiolini, M.; Feraco, E.; Mari, V.; Franceschi, C.; Passarino, G.; et al. (Genomics, 2005)

(untitled) - Serrano, L.; Martínez-Redondo, P.; Marazuela-Duque, A.; Vazquez, B. N.; Dooley, S. J.; Voigt, P.; Beck, D. B.; Kane-Goldsmith, N.; Tong, Q.; Rabanal, R. M.; Fondevila, D.; Muñoz, P.; et al. (Genes Dev., 2013)

(untitled) - Cameron, D.; Eisler, S. (J. Phys. Org. Chem., 2018)

(untitled) - Suzuki, H. (Bull. Chem. Soc. Jpn., 1952)

(untitled) - Bandara, H. M. D.; Burdette, S. C. (Chem. Soc. Rev., 2012)

(untitled) - Cammenga, H. K.; Emel’yanenko, V. N.; Verevkin, S. P. (Ind. Eng. Chem. Res., 2009)

(untitled) - Meier, H. (Angew. Chem., Int. Ed. Engl., 1992)

(untitled) - Han, W.-G.; Lovell, T.; Liu, T.; Noodleman, L. (ChemPhysChem, 2002)

(untitled) - Irie, M. (Chem. Rev., 2000)

(untitled) - Chung, J. W.; Yoon, S.-J.; An, B.-K.; Park, S. Y. (J. Phys. Chem. C, 2013)

(untitled) - Lerch, M. M.; Hansen, M. J.; van Dam, G. M.; Szymanski, W.; Feringa, B. L. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hüll, K.; Morstein, J.; Trauner, D. (Chem. Rev., 2018)

(untitled) - Hoorens, M. W. H.; Szymanski, W. (Trends Biochem. Sci., 2018)

(untitled) - Tochitsky, I.; Kienzler, M. A.; Isacoff, E.; Kramer, R. H. (Chem. Rev., 2018)

(untitled) - Szymański, W.; Beierle, J. M.; Kistemaker, H. A. V.; Velema, W. A.; Feringa, B. L. (Chem. Rev., 2013)

(untitled) - Crespi, S.; Simeth, N. A.; König, B. (Nat. Rev. Chem., 2019)

(untitled) - Trapp, J.; Jochum, A.; Meier, R.; Saunders, L.; Marshall, B.; Kunick, C.; Verdin, E.; Goekjian, P.; Sippl, W.; Jung, M. (J. Med. Chem., 2006)

(untitled) - Falenczyk, C.; Schiedel, M.; Karaman, B.; Rumpf, T.; Kuzmanovic, N.; Grøtli, M.; Sippl, W.; Jung, M.; König, B. (Chem. Sci., 2014)

(untitled) - McDonald, O.; Lackey, K.; Davis-Ward, R.; Wood, E.; Samano, V.; Maloney, P.; Deanda, F.; Hunter, R. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Swyter, S.; Schiedel, M.; Monaldi, D.; Szunyogh, S.; Lehotzky, A.; Rumpf, T.; Ovádi, J.; Sippl, W.; Jung, M. (Philos. Trans. R. Soc., B, 2018)

(untitled) - Buettelmann, B.; Alanine, A.; Bourson, A.; Gill, R.; Heitz, M.-P.; Mutel, V.; Pinard, E.; Trube, G.; Wyler, R. (Chimia, 2004)

Palladium reagents in organic syntheses - Heck, R. F. (Academic Press, 1990)

(untitled) - Heltweg, B.; Trapp, J.; Jung, M. (Methods, 2005)

(untitled) - Cui, H.; Kamal, Z.; Ai, T.; Xu, Y.; More, S. S.; Wilson, D. J.; Chen, L. (J. Med. Chem., 2014)

(untitled) - Ai, T.; Wilson, D. J.; More, S. S.; Xie, J.; Chen, L. (J. Med. Chem., 2016)

(untitled) - Schiedel, M.; Rumpf, T.; Karaman, B.; Lehotzky, A.; Oláh, J.; Gerhardt, S.; Ovádi, J.; Sippl, W.; Einsle, O.; Jung, M. (J. Med. Chem., 2016)

(untitled) - Rumpf, T.; Schiedel, M.; Karaman, B.; Roessler, C.; North, B. J.; Lehotzky, A.; Oláh, J.; Ladwein, K. I.; Schmidtkunz, K.; Gajer, M.; Pannek, M.; Steegborn, C.; et al. (Nat. Commun., 2015)

(untitled) - Suzuki, T.; Khan, M. N. A.; Sawada, H.; Imai, E.; Itoh, Y.; Yamatsuta, K.; Tokuda, N.; Takeuchi, J.; Seko, T.; Nakagawa, H.; Miyata, N. (J. Med. Chem., 2012)

(untitled) - Sundriyal, S.; Moniot, S.; Mahmud, Z.; Yao, S.; Di Fruscia, P.; Reynolds, C. R.; Dexter, D. T.; Sternberg, M. J. E.; Lam, E. W.-F.; Steegborn, C.; Fuchter, M. J. (J. Med. Chem., 2017)

(untitled) - Huang, S.; Song, C.; Wang, X.; Zhang, G.; Wang, Y.; Jiang, X.; Sun, Q.; Huang, L.; Xiang, R.; Hu, Y.; Li, L.; Yang, S. (J. Chem. Inf. Model., 2017)

(untitled) - Robaa, D.; Monaldi, D.; Wössner, N.; Kudo, N.; Rumpf, T.; Schiedel, M.; Yoshida, M.; Jung, M. (Chem. Rec., 2018)

(untitled) - Smakula, A. (Z. Phys. Chem., 1934)

(untitled) - Buckles, R. E. (J. Am. Chem. Soc., 1955)

(untitled) - Ciamician, G.; Silber, P. (Ber. Dtsch. Chem. Ges., 1902)

(untitled) - Lewis, F. D.; Kalgutkar, R. S.; Yang, J.-S. (J. Am. Chem. Soc., 2001)

(untitled) - Christiansen, O.; Koch, H.; Jørgensen, P. (Chem. Phys. Lett., 1995)

(untitled) - Hättig, C.; Köhn, A. (J. Chem. Phys., 2002)

(untitled) - Hättig, C. (Adv. Quantum Chem., 2005)

(untitled) - Klamt, A.; Schüürmann, G. (J. Chem. Soc., Perkin Trans. 2, 1993)

(untitled) - Lunkenheimer, B.; Köhn, A. (J. Chem. Theory Comput., 2013)

(untitled) - Send, R.; Kühn, M.; Furche, F. (J. Chem. Theory Comput., 2011)

(untitled) - Broichhagen, J.; Frank, J. A.; Trauner, D. (Acc. Chem. Res., 2015)

(untitled) - Schoenberger, M.; Damijonaitis, A.; Zhang, Z.; Nagel, D.; Trauner, D. (ACS Chem. Neurosci., 2014)

(untitled) - Morstein, J.; Awale, M.; Reymond, J.-L.; Trauner, D. (ACS Cent. Sci., 2019)

(untitled) - Hauwert, N. J.; Mocking, T. A. M.; Da Costa Pereira, D.; Lion, K.; Huppelschoten, Y.; Vischer, H. F.; De Esch, I. J. P.; Wijtmans, M.; Leurs, R. (Angew. Chem., Int. Ed., 2019)

(untitled) - Hauwert, N. J.; Mocking, T. A. M.; Da Costa Pereira, D.; Lion, K.; Huppelschoten, Y.; Vischer, H. F.; De Esch, I. J. P.; Wijtmans, M.; Leurs, R. (Angew. Chem., 2019)

(untitled) - Simeth, N. A.; Bellisario, A.; Crespi, S.; Fagnoni, M.; König, B. (J. Org. Chem., 2019)

(untitled) - Schehr, M.; Ianes, C.; Weisner, J.; Heintze, L.; Müller, M. P.; Pichlo, C.; Charl, J.; Brunstein, E.; Ewert, J.; Lehr, M.; Baumann, U.; Rauh, D.; et al. (Photochem. Photobiol. Sci., 2019)

(untitled) - Rustler, K.; Maleeva, G.; Bregestovski, P.; König, B. (Beilstein J. Org. Chem., 2019)

(untitled) - Schiedel, M.; Herp, D.; Hammelmann, S.; Swyter, S.; Lehotzky, A.; Robaa, D.; Oláh, J.; Ovádi, J.; Sippl, W.; Jung, M. (J. Med. Chem., 2018)

(untitled) - Laemmli, U. K. (Nature, 1970)

TURBOMOLE, V7.2 2017 (University of Karlsruhe and Forschungszentrum Karlsruhe GmbH, TURBOMOLE GmbH, 2007)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Schäfer, A.; Horn, H.; Ahlrichs, R. (J. Chem. Phys., 1992)

(untitled) - Perdew, J. P.; Ernzerhof, M.; Burke, K. (J. Chem. Phys., 1996)

(untitled) - Bauernschmitt, R.; Ahlrichs, R. (Chem. Phys. Lett., 1996)

(untitled) - Furche, F.; Ahlrichs, R. (J. Chem. Phys., 2002)

(untitled) - Eichkorn, K.; Weigend, F.; Treutler, O.; Ahlrichs, R. (Theor. Chem. Acc., 1997)

(untitled) - De Haan, D. O.; Tapavicza, E.; Riva, M.; Cui, T.; Surratt, J. D.; Smith, A. C.; Jordan, M.-C.; Nilakantan, S.; Almodovar, M.; Stewart, T. N.; de Loera, A.; De Haan, A. C.; et al. (Environ. Sci. Technol., 2018)

(untitled) - Thompson, T.; Tapavicza, E. (J. Phys. Chem. Lett., 2018)

(untitled) - Tapavicza, E.; Thompson, T.; Redd, K.; Kim, D. (Phys. Chem. Chem. Phys., 2018)

(untitled) - Mashimo, S.; Kuwabara, S.; Yagihara, S.; Higasi, K. (J. Chem. Phys., 1989)

(untitled) - Herráez, J. V.; Belda, R. (J. Solution Chem., 2006)

(untitled) - Epstein, S. A.; Tapavicza, E.; Furche, F.; Nizkorodov, S. A. (Atmos. Chem. Phys., 2013)

(untitled) - Schalk, O.; Geng, T.; Thompson, T.; Baluyot, N.; Thomas, R. D.; Tapavicza, E.; Hansson, T. (J. Phys. Chem. A, 2016)

(untitled) - Cisneros, C.; Thompson, T.; Baluyot, N.; Smith, A. C.; Tapavicza, E. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Tapavicza, E.; Furche, F.; Sundholm, D. (J. Chem. Theory Comput., 2016)